Clinical and economic impact of partnered pharmacist medication charting in the emergency department - Atey, Tesfay Mehari; Peterson, Gregory M.; Salahudeen, Mohammed S.; Simpson, Tom; Boland, Camille M.; Anderson, Ed; Wimmer, Barbara C. (Frontiers in Pharmacology, 2023)
Introduction Partnered pharmacist medication charting (PPMC), a process redesign hypothesised to improve medication safety and interdisciplinary collaboration, was trialed in a tertiary hospital’s emergency department (ED). Objective To evaluate the health-related impact and economic benefit of PPMC. Methods A pragmatic, controlled study compared PPMC to usual care in the ED. PPMC included pharmacist-documented best-possible medication history (BPMH), followed by a clinical conversation between a pharmacist and a medical officer to jointly develop a treatment plan and chart medications. Usual care included a medical officer-led traditional medication charting in the ED, without a pharmacist-obtained BPMH or clinical conversation. Outcome measures, assessed after propensity score matching, were length of hospital or ED stay, relative stay index (RSI), in-hospital mortality, 30-day hospital readmissions or ED revisits, and cost. Results A total of 309 matched pairs were analysed. The median RSI was reduced by 15.4% with PPMC (p = 0.029). There were no significant differences between the groups in the median length of ED stay (8 vs. 10 hours, p = 0.52), in-hospital mortality (1.3% vs 1.3%, p > 0.99), 30-day readmission rates (21% vs 17%; p = 0.35) and 30-day ED revisit rates (21% vs 19%; p = 0.68). The hospital spent approximately $282.4 for the cost of PPMC care per patient to avert at least one medication error bearing high/extreme risk. PPMC saved approximately $1233 on the average cost of each admission. Conclusion Implementing the ED-based PPMC model was associated with a significantly reduced RSI and admission costs, but did not affect clinical outcomes.